Naturalizing Technology, Technologizing Nature: On the Global Political Ecology of Smart Environments - Purwins, Sebastian; Pieper, Maximilian; Walter, Christina (DIE ERDE – Journal of the Geographical Society of Berlin, 2026)
We critically examine how integrating sensor-based technologies into urban green infrastructures—exemplified by smart trees in Augsburg (Germany) equipped with soil moisture sensors—both reshapes and re-politicizes the relationship between humans, nature, and data. Terms such as The Internet of Nature or the Wood Wide Web naturalize the data-driven management practices of smart forestry and frame them as neutral means for environmental protection. However, this overlooks the ways in which data is produced, interpreted, and embedded in specific sociotechnical configurations that are anything but neutral. Drawing from political ecology, science and technology studies, and Niklas Luhmann’s concept of functional simplification, we argue that well-known critiques of instrumentalizing nature do not sufficiently grasp what is happening when we increasingly come to rely on digital technologies to secure ecosystem services. Instead, we plead for understanding these developments as a technologization of nature. As environmental conditions become increasingly unstable due to climate change, reliable ecosystem functioning must be artificially maintained. In practice, this means isolating and optimizing selected causal relationships—such as a tree’s water intake—to ensure reliable performance. This approach transforms once self-sustaining ecological processes into engineered systems, masked in the rhetoric of natural networks. Moreover, the global political economy that enables these smart interventions disproportionately favors the wealthy regions of the Global North, whose technological infrastructures depend on unequal resource extraction and labor conditions elsewhere. Thus, while datafication and sensor technologies may enhance certain aspects of urban resilience, they do so in ways that reinforce inequalities. At the same time, their naturalization obscures the complex, socially contested arrangements that underpin these newly technologized ecosystems.